Integral transform methods for solving fractional dynamic equations on time scales - Segi Rahmat, Mohamad Rafi (Hindawi Publishing Corporation, 2014)
We introduce nabla type Laplace transform and Sumudu transform on general time scales. We investigate the properties and the applicability of these integral transforms and their efficiency in solving fractional dynamic equations on time scales.